Endogenous Investment Decisions in Natural Gas Equilibrium Models with Logarithmic Cost Functions - Daniel Huppmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The liberalisation of the natural gas markets and the importance of natural gas as a transition fuel to a low-carbon economy have led to the development of several large-scale equilibrium models in the last decade. These models combine long-term market equilibria and investments in infrastructure while accounting for market power by certain suppliers. They are widely used to simulate market outcomes given different scenarios of demand and supply development, environmental regulations and investment options. In order to capture the specific characteristics of natural gas production, most of these models apply a logarithmic production cost function. However, no model has so far combined this cost function type with endogenous investment decisions in production capacity. Given the importance of capacity constraints in the determination of the natural gas supply, this is a serious shortcoming of the current literature. This paper provides a proof that combining endogenous investment decisions and a logarithmic cost function yields indeed a convex minimization problem, paving the way for an important extension of current state-of-the-art equilibrium models.
Keywords: C61; Q41; L71; 330; natural gas; equilibrium model; endogenous investment; capacity expansion; logarithmic cost function